Integrated perception-communication-logistics multi-objective oriented path planning for emergency UAVs - XU Yunpeng; XIE Yaqi; YU Ran; HOU Luyang; WANG Kailiang; XU Lianming (Tongxin xuebao)
In order to complete the tasks of demand perception (perception), data collection (communication), and material delivery (logistics) at disaster relief sites in multi-UAV emergency scenarios, a two-stage solution framework was proposed for multi-UAV path planning that integrated perception, communication, and logistics objective considering UAV energy consumption constraint. In the first stage, a temporal graph convolution networks-based model was introduced to predict the number of personnel at the relief sites to quantify its supply and communication needs. In the second stage, a multi-UAV path planning algorithm based on the greedy and tabu search was proposed to solve the optimization problem through iteratively optimizing the relief point clustering and the path planning of individual UAV. The simulation results demonstrate that the proposed algorithm is superior to the traditional prediction-free multi-UAV path planning algorithm in terms of the total service revenue.